STUDY OF BEHAVIOURAL AND MORPHOLOGICAL ANOMALIES OF FRY FISH OF FRESH WATER TELEOST, CHANNA PUNCTATUS UNDER CHLORPYRIFOS INTOXICATION - YOGITA DEVI; ABHA MISHRA (International Journal of Pharma and Bio Sciences, 2013)
The present study was conduct to assess the effect of Chlorpyrifos toxicity to behavioural and morphological manifestation of fry fish of Channa punctatus. The mortality data obtained through probit analysis was found to 0.365, 0.328, 0.269, and 0.253µl/l at 24th, 48th, 72nd, and 96th hrs respectively. The change in behaviour of fish such as convulsions, swimming erratically, vertical hanging, coughing, loss of balance, abnormal opercular movement, and lateral flexure, with tail beat were shown and finally fish became lethargic and settled at the bottom and their belly turned up before death. Opercular beat frequency (OBF/ min.), tail beat frequency (TBF/ min.), in gulping air or escaping attempt / min. and surfacing at sec. Increased with increasing concentration of CPF up to 24 hrs after that decreased following 96 hrs of exposure tenure. These quantal behaviour responses were significant at p<0.001.The prevalence of morphological deformities such as shedding of scales, discoloration, lesion of skin, split and necrosis of fins, eye deformities, scoliosis, damaged skull, lower lip extension and copious amount of mucus secretion all over the body were shown. The percentage of these deformities was dose and duration dependent.